TRAINING OF PHYSICAL THERAPY SPECIALISTS: MODERN APPROACHES - Губенко, Інна; Степанова, Галина; Шевченко, Василь (SWorldJournal, 2025)
Introduction. The paper examines the contemporary approaches to training physical therapy specialists amid growing demand for rehabilitation services and medical field globalization. The ongoing technological innovations and rising quality standards neces